Laminate
Patent Information
- Application Number
- JP2023125612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0007】 本発明によれば、剛性に優れる積層体が提供される。
Smart Images

Figure 2025021705000004 
Figure 2025021705000005 
Figure 2025021705000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber width of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products. As fibrous cellulose, fine fibrous cellulose with a fiber width of 1,000 nm or less is also known. In addition, sheets made of such fine fibrous cellulose, composite sheets containing fine fibrous cellulose and resin, and molded articles have been developed. It is known that in sheets and molded articles containing fine fibrous cellulose, the number of contact points between fibers increases significantly, and therefore the tensile strength is greatly improved. Patent Document 1 discloses a polycarbonate resin / cellulose fiber laminate comprising a polycarbonate resin layer and a cellulose fiber layer, in which the thickness of the polycarbonate resin layer is 1.4 times or more the thickness of the cellulose fiber layer, with the aim of providing a composite that has high transparency, high elasticity, a low linear expansion coefficient, and a good balance of properties such as impact resistance, and that is also easy to produce, by laminating a polycarbonate resin layer and a cellulose fiber layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4985573 Summary of the Invention [Problem to be solved by the invention]
[0004] Since the fine fibrous cellulose-containing sheet has excellent mechanical strength such as tensile strength and also has excellent transparency, it can be used as a laminate in combination with a resin layer, etc., for various display devices, optical components such as various solar cells, and window materials for various vehicles and buildings. When used for such purposes, in order to further improve the quality of the product, it is desirable for the laminate to have higher rigidity, i.e., bending strength and bending modulus, than conventional laminates. Therefore, an object of the present invention is to provide a laminate having excellent rigidity. [Means for solving the problem]
[0005] The inventors have discovered that the above problem can be solved by a laminate comprising a core resin plate containing a polycarbonate-based resin, on one side of which are laminated, in that order, an adhesive layer 1A, a fine fibrous cellulose-containing layer 1 containing fine fibrous cellulose with a fiber width of 1000 nm or less, an adhesive layer 1B, and a resin film 1, and on the side opposite to the side of the core resin plate having resin film 1, are laminated, in that order, from the core resin plate, and in which the tensile modulus of the core resin plate, the tensile modulus of the resin film 1, and the tensile modulus of the resin film 2 have a specific relationship.
[0006] That is, the present invention provides the following: <1> ~ <14> Regarding. <1> A laminate comprising: an adhesive layer 1A, a fine fibrous cellulose-containing layer 1 containing fine fibrous cellulose having a fiber width of 1000 nm or less, an adhesive layer 1B, and a resin film 1 laminated in this order on one surface of a core resin plate; and an adhesive layer 2 and a resin film 2 laminated in this order on the surface of the core resin plate opposite to the surface having the resin film 1, The core resin plate contains polycarbonate resin, A laminate in which the tensile modulus of elasticity of resin film 1 and the tensile modulus of elasticity of resin film 2 are greater than the tensile modulus of elasticity of the core resin plate. <2> The tensile modulus of elasticity of the resin film 1 and the tensile modulus of elasticity of the resin film 2 are 0.5 GPa or more greater than the tensile modulus of elasticity of the core resin plate; <1> The laminate according to claim 1. <3> Resin film 1 and resin film 2 contain at least one selected from the group consisting of polyethylene terephthalate and polymethyl methacrylate. <1> or <2> The laminate according to claim 1. <4> The adhesive layer 1A and the adhesive layer 1B contain at least one selected from the group consisting of a polycarbonate-based resin, an acrylic-based resin, and a polyester-based resin. <1> ~ <3> 13. The laminate according to claim 12 . <5> The adhesive layer 1A and the adhesive layer 1B are formed from an adhesive composition containing an isocyanate compound. <1> ~ <4> 13. The laminate according to claim 12 . <6> The thickness of the core resin plate is 500 μm or more and 3,500 μm or less. <1> ~ <5> 13. The laminate according to claim 12 . <7> The thickness of the fine fibrous cellulose-containing layer 1 is 20 μm or more and 300 μm or less. <1> ~ <6> 13. The laminate according to claim 12 . <8> The thickness of the resin film 1 is 30 μm or more and 500 μm or less. <1> ~ <7> 13. The laminate according to claim 12 . <9> On the surface of the core resin plate opposite to the surface having the resin film 1, an adhesive layer 2A, a fine fibrous cellulose-containing layer 2 containing fine fibrous cellulose having a fiber width of 1000 nm or less, an adhesive layer 2B, and a resin film 2 are laminated in this order from the core resin plate. <1> ~ <8> 13. The laminate according to claim 12 . <10> The adhesive layer 2A and the adhesive layer 2B contain at least one selected from the group consisting of a polycarbonate-based resin, an acrylic-based resin, and a polyester-based resin. <9> The laminate according to claim 1. <11> The adhesive layer 2A and the adhesive layer 2B are formed from an adhesive composition containing an isocyanate compound. <9> or <10> The laminate according to claim 1. <12> The thickness of the fine fibrous cellulose-containing layer 2 is 20 μm or more and 250 μm or less. <9> ~ <11> 13. The laminate according to claim 12 . <13> The thickness of the resin film 2 is 30 μm or more and 500 μm or less. <1> ~ <12> 13. The laminate according to claim 12 . <14> The flexural modulus is 3.4 GPa or more. <1> ~ <13> 13. The laminate according to claim 12 . Effect of the Invention
[0007] According to the present invention, a laminate having excellent rigidity is provided. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 2] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described. In this specification, "X to Y" indicating a range means "X or more and Y or less". In this specification, the upper and lower limits of the numerical ranges can be combined arbitrarily. In this specification, the components contained or may be contained in each layer constituting the laminate may be used alone or in combination of two or more.
[0010] [Laminate] The laminate of this embodiment is formed by laminating, in this order, adhesive layer 1A, fine fibrous cellulose-containing layer 1 containing fine fibrous cellulose having a fiber width of 1000 nm or less, adhesive layer 1B, and resin film 1 on one side of a core resin plate, and has, in this order, adhesive layer 2 and resin film 2 on the side of the core resin plate opposite to the side having resin film 1, the core resin plate containing a polycarbonate-based resin, and the tensile modulus of elasticity of resin film 1 and the tensile modulus of elasticity of resin film 2 are greater than the tensile modulus of elasticity of the core resin plate. The laminate of the present embodiment has excellent rigidity, and further has additional effects of being resistant to yellowing, excellent in total light transmittance and haze, and a small coefficient of linear thermal expansion.
[0011] In the laminate of this embodiment, from the viewpoint of improving the rigidity of the laminate, the tensile modulus of the resin film 1 is preferably 0.5 GPa or more larger than the tensile modulus of the core resin plate, more preferably 0.8 GPa or more larger, even more preferably 1.1 GPa or more larger, even more preferably 1.4 GPa or more larger, and particularly preferably 1.7 GPa or more larger. The upper limit of the difference between the tensile modulus of the resin film 1 and the tensile modulus of the core resin plate ("tensile modulus of the resin film 1" - "tensile modulus of the core resin plate") is not particularly limited, but from the viewpoint of ease of manufacture, it is, for example, 3.0 GPa or less. In the laminate of this embodiment, from the viewpoint of improving the rigidity of the laminate, the tensile modulus of the resin film 2 is preferably 0.5 GPa or more larger than the tensile modulus of the core resin plate, more preferably 0.8 GPa or more larger, even more preferably 1.1 GPa or more larger, even more preferably 1.4 GPa or more larger, and particularly preferably 1.7 GPa or more larger. The upper limit of the difference between the tensile modulus of the resin film 2 and the tensile modulus of the core resin plate ("tensile modulus of the resin film 2" - "tensile modulus of the core resin plate") is not particularly limited, but from the viewpoint of ease of manufacture, it is, for example, 3.0 GPa or less.
[0012] The laminate of this embodiment may have at least an adhesive layer and a resin film 2, in that order, on the side of the laminate opposite to the side having the resin film 1. From the viewpoint of improving the rigidity of the laminate, however, it is preferable that the side of the core resin plate opposite to the side having the resin film 1 has an adhesive layer 2A, a fine fibrous cellulose-containing layer 2 containing fine fibrous cellulose having a fiber width of 1000 nm or less, an adhesive layer 2B, and a resin film 2 laminated in that order from the core resin plate. This embodiment will be described in further detail below.
[0013] [Core resin plate] The laminate of this embodiment has a core resin plate. The core resin plate contains a polycarbonate-based resin. The term "polycarbonate-based resin" refers to a resin containing a site in which structural units are repeatedly bonded via a carbonate group (-O-(C=O)-O-). From the viewpoint of improving the rigidity of the laminate, the content of polycarbonate-based resin in the core resin plate is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and 100% by mass or less. The core resin plate may contain, in addition to the polycarbonate resin, for example, an acrylonitrile butadiene styrene copolymer or a polymethyl methacrylate resin.
[0014] <Thickness> The thickness of the core resin plate in this embodiment is preferably 200 μm or more, more preferably 500 μm or more, even more preferably 1,000 μm or more, even more preferably 1,500 μm or more, even more preferably 2,000 μm or more, even more preferably 2,500 μm or more, particularly preferably 2,800 μm or more, and is preferably 5,000 μm or less, more preferably 4,500 μm or less, even more preferably 4,000 μm or less, even more preferably 3,500 μm or less, particularly preferably 3,200 μm or less. The thickness of the core resin plate is preferably adjusted appropriately depending on the application of the laminate.
[0015] <Tensile modulus> The tensile modulus of the core resin plate in this embodiment is preferably 1.0 GPa or more, more preferably 1.5 GPa or more, and even more preferably 2.0 GPa or more from the viewpoint of improving the rigidity of the laminate, and is preferably 3.5 GPa or less, more preferably 3.0 GPa or less, and even more preferably 2.5 GPa or less from the viewpoint of ease of manufacture of the laminate. The tensile modulus of the core resin plate in this embodiment is a value obtained in accordance with JIS K 7161-2:2014. The test piece used for the tensile modulus can be obtained by cutting from the raw core resin plate or the core resin plate in the laminate. In addition, the polymer constituting the core resin plate in the laminate may be identified by spectral analysis such as infrared absorption spectroscopy, and the polymer may be used to prepare a test piece having the same thickness as the core resin plate in the laminate.
[0016] [Adhesive layer 1A, 1B, 2, 2A, 2B] As described above, the laminate of this embodiment has adhesive layers 1A and 1B on one side of the core resin plate, and adhesive layer 2 on the other side of the core resin plate. In addition, the laminate of this embodiment preferably has adhesive layers 2A and 2B on the other side of the core resin plate. The components contained and the components that can be contained in each of the adhesive layers 1A, 1B, 2, 2A, and 2B may be the same or different, but it is preferable that they are the same. Note that the preferred forms of the components contained and the components that can be contained in each of the adhesive layers 1A, 1B, 2, 2A, and 2B are the same. Hereinafter, adhesive layers 1A, 1B, 2, 2A and 2B are also collectively referred to simply as "adhesive layers".
[0017] Examples of adhesives constituting the adhesive layer include polycarbonate-based resins, acrylic-based resins, polyester-based resins, vinyl chloride resins, vinyl acetate resins, urethane resins, silicone resins, epoxy resins, ethylene / vinyl acetate copolymer resins, polyvinyl alcohol resins, ethylene-vinyl alcohol copolymer resins, and rubber emulsions such as SBR and NBR. One or more selected from the group consisting of polycarbonate-based resins, acrylic-based resins, and polyester-based resins are preferred, and polycarbonate-based resins are more preferred. As the polycarbonate-based resin, for example, the polycarbonate copolymer described in JP-A-2008-24919 can be used.
[0018] The adhesive layer is preferably formed from an adhesive composition containing an adhesive aid (formed using an adhesive composition containing an adhesive aid). Examples of the adhesive aid include compounds containing at least one selected from an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, and a silanol group. Among them, the adhesive aid is preferably a compound containing an isocyanate group (isocyanate compound).
[0019] The adhesive composition preferably contains an adhesive and an adhesive aid, preferably contains one or more resins selected from the group consisting of polycarbonate-based resins, acrylic-based resins, and polyester-based resins, and an isocyanate compound, and more preferably contains a polycarbonate-based resin and an isocyanate compound.
[0020] In the adhesive composition, the content of the adhesive aid per 100 parts by mass of the adhesive is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and preferably 30 parts by mass or less, more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less.
[0021] The adhesive composition preferably contains an organic solvent, such as toluene, methylene chloride, tetrahydrofuran, tetraglyme, dimethyl carbonate, methyl ethyl ketone, ethyl acetate, dimethylacetamide, and styrene.
[0022] The solids concentration of the adhesive composition is preferably 1 mass% or more, more preferably 4 mass% or more, even more preferably 7 mass% or more, and preferably 25 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less.
[0023] [Fine fibrous cellulose-containing layers 1 and 2] As described above, the laminate of this embodiment has a fine fibrous cellulose-containing layer 1 containing fine fibrous cellulose with a fiber width of 1000 nm or less on one side of the core resin plate. In addition, the laminate of this embodiment preferably has a fine fibrous cellulose-containing layer 2 containing fine fibrous cellulose with a fiber width of 1000 nm or less on the other side of the core resin plate. The components contained in the fine fibrous cellulose-containing layer 1 and the components that can be contained therein, as well as the thickness, basis weight and density of the fine fibrous cellulose-containing layer 1, and the components contained in the fine fibrous cellulose-containing layer 2 and the components that can be contained therein, as well as the thickness, basis weight and density of the fine fibrous cellulose-containing layer 2 may be the same or different from each other, but are preferably the same. The preferred form described below is the same for the fine fibrous cellulose-containing layer 1 and the fine fibrous cellulose-containing layer 2. Hereinafter, the fine fibrous cellulose-containing layers 1 and 2 will be collectively referred to simply as the "fine fibrous cellulose-containing layers."
[0024] <Fine fibrous cellulose> Fine fibrous cellulose is fibrous cellulose having a fiber width of 1,000 nm or less. The fiber width of fibrous cellulose can be measured, for example, by observation using an electron microscope. The fiber width of the fine fibrous cellulose is 1,000 nm or less. The fiber width of the fine fibrous cellulose is, for example, preferably 2 nm or more and 1,000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the fiber width of the fine fibrous cellulose 2 nm or more, it is possible to suppress dissolution of the cellulose molecules in water, and to more easily realize the effect of improving the strength, rigidity, and dimensional stability of the fine fibrous cellulose.
[0025] The average fiber width of the fine fibrous cellulose is, for example, 1,000 nm or less. The average fiber width of the fine fibrous cellulose is preferably 2 nm or more and 1,000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the average fiber width of the fine fibrous cellulose 2 nm or more, it is possible to suppress dissolution of the cellulose molecules in water, and to more easily realize the effect of improving the strength, rigidity, and dimensional stability of the fine fibrous cellulose. The fine fibrous cellulose is, for example, a single-fiber cellulose.
[0026] The number-average fiber width of fine fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.01% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for observation with a transmission electron microscope (TEM). When wide fibers are included, a scanning electron microscope (SEM) image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1,000x, 5,000x, 10,000x, or 50,000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.
[0027] For the observation images that satisfy the above conditions, the width of the fibers that intersect with the lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with the lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average of the read fiber widths is then determined as the number average fiber width of the fibrous cellulose.
[0028] The fiber length of the fine fibrous cellulose is not particularly limited, but is preferably, for example, 0.1 μm to 1,000 μm, more preferably 0.1 μm to 800 μm, and even more preferably 0.1 μm to 600 μm. By setting the fiber length within the above range, destruction of the crystalline region of the fine fibrous cellulose can be suppressed. It is also possible to set the slurry viscosity of the fine fibrous cellulose to an appropriate range. The fiber length of the fine fibrous cellulose can be determined by image analysis using, for example, TEM, SEM, or atomic force microscope (AFM).
[0029] The fine fibrous cellulose preferably has a type I crystal structure. The fact that the fine fibrous cellulose has a type I crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromated with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This is expected to provide even better performance in terms of low linear thermal expansion coefficient. The degree of crystallinity is determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0030] The axial ratio (fiber length / fiber width) of the fine fibrous cellulose is not particularly limited, but is preferably, for example, 20 to 10,000, and more preferably 50 to 1,000. By setting the axial ratio to the above lower limit or more, a sheet containing the fine fibrous cellulose can be easily formed. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fine fibrous cellulose is treated as an aqueous dispersion, handling such as dilution is facilitated.
[0031] In the present embodiment, the fine fibrous cellulose preferably has at least one of an ionic substituent and a nonionic substituent. From the viewpoint of improving the dispersibility of the fibers in the dispersion medium and increasing the defibration efficiency in the defibration treatment, it is more preferable that the fine fibrous cellulose has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In addition, the nonionic substituent may include, for example, an alkyl group and an acyl group. In the present embodiment, it is particularly preferable that the ionic substituent has an anionic group. In addition, the ionic substituent is preferably a group that is introduced into the fine fibrous cellulose via an ester bond or an ether bond, and more preferably a group that is introduced into the fine fibrous cellulose via an ester bond. In this case, the ester bond is preferably formed by dehydration condensation of the fine fibrous cellulose and a compound that becomes an ionic substituent. The fine fibrous cellulose does not necessarily need to be subjected to a treatment for introducing an ionic substituent.
[0032] Examples of anionic groups as ionic substituents include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxy groups or substituents derived from carboxy groups (sometimes simply referred to as carboxy groups), sulfur oxoacid groups or substituents derived from sulfur oxoacid groups (sometimes simply referred to as sulfur oxoacid groups), xanthate groups or substituents derived from xanthate groups (sometimes simply referred to as xanthate groups), phosphonic groups or substituents derived from phosphonic groups, phosphine groups or substituents derived from phosphine groups, sulfone groups or substituents derived from sulfone groups, and carboxyalkyl groups. Among them, the anionic group is preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, carboxymethyl group, carboxyethyl group, sulfur oxo acid group and sulfur oxo acid group, xanthate group, and substituents derived from sulfone group, more preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, sulfur oxo acid group, substituents derived from sulfur oxo acid group, and xanthate group, more preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, sulfur oxo acid group, and substituents derived from sulfur oxo acid group, and particularly preferably phosphorus oxo acid group. By introducing a phosphorus oxo acid group as an anionic group, for example, even under alkaline conditions or acidic conditions, the dispersibility of fibrous cellulose can be further increased, and as a result, a high-strength and highly transparent fine fibrous cellulose-containing layer is easily obtained. Examples of the cationic group as the ionic substituent include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group.
[0033] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of substituents represented by the following formula (1) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0034] [ka]
[0035] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of n α and α′ (preferably a) is O. - and the rest are R or OR. Note that each α and α' is O. - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances. Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In addition, α in formula (1) may be a group derived from a cellulose molecular chain. In addition, in formula (1), n is preferably 1.
[0036] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups. In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO- ), a hydroxy group, an amino group, and other functional groups may be added or substituted with at least one functional group, but is not particularly limited thereto. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set within an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine fibrous cellulose. When multiple Rs are present in formula (1) or multiple types of substituents represented by the above formula (1) are introduced into the fine fibrous cellulose, the multiple Rs may be the same or different.
[0037] β b+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is, but is not limited to, an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. These may be used alone or in combination of two or more kinds. In addition, β in formula (1) b+ When a plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0038] More specifically, the phosphorus oxo acid group or a substituent derived from the phosphorus oxo acid group is a phosphoric acid group (-PO 3 H 2 ), salts of phosphoric acid groups, phosphorous acid groups (phosphonic acid groups) (-PO 2 H 2 ), and salts of phosphorous acid group (phosphonic acid group). The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphoric acid group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0039] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of types of substituents represented by the following formula (2) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0040] [ka]
[0041] In formula (2), b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different numbers. In formula (2), β b+is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. When multiple types of substituents represented by the above formula (2) are introduced into the fine fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0042] The amount of ionic substituent introduced into the fine fibrous cellulose is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of ionic substituent introduced into the fine fibrous cellulose is preferably 5.20 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.50 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of ionic substituent (preferably anionic group) introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fine fibrous cellulose. Here, the denominator in the unit mmol / g is the counter ion of the ionic substituent, which is a hydrogen ion (H + ) indicates the mass of the fine fibrous cellulose when
[0043] In addition, the amount of ionic substituent (preferably anionic group) introduced into the fine fibrous cellulose is preferably less than 0.50 mmol / g per 1 g (mass) of fine fibrous cellulose from the viewpoint of water absorption of the laminate, more preferably 0.40 mmol / g or less, even more preferably 0.30 mmol / g or less, even more preferably 0.25 mmol / g or less, and particularly preferably 0.15 mmol / g or less, and from the viewpoint of total light transmittance and haze of the laminate, it is preferably 0.01 mmol / g or more, more preferably 0.02 mmol / g or more, and even more preferably 0.03 mmol / g or more. Such a low amount of substituent fine fibrous cellulose may be obtained, for example, by subjecting fine fibrous cellulose to a treatment for removing substituents, as described later.
[0044] The amount of ionic substituent introduced into the fine fibrous cellulose can be measured, for example, by neutralization titration. In the measurement by neutralization titration, an alkali such as an aqueous sodium hydroxide solution is added to the obtained slurry containing the fine fibrous cellulose, and the amount introduced is measured by determining the change in pH.
[0045] 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 1 is obtained. In the titration curve shown in the upper part of Figure 1, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 1, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH against the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxo acid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxo acid group introduced (or the amount of phosphorus oxo acid group), it refers to the amount of the first dissociated acid. In FIG. 1, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum. The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (sum of the amount of strong acidic groups and weak acidic groups in phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0046] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto the fine fibrous cellulose having a carboxy group and the pH. The amount of carboxyl groups introduced into the fine fibrous cellulose is measured, for example, as follows. First, a slurry containing fine fibrous cellulose is treated with a strong acid ion exchange resin. If necessary, the measurement object may be subjected to a defibration treatment similar to the defibration treatment process described below before the treatment with the strong acid ion exchange resin. Next, the change in pH is observed while adding an aqueous sodium hydroxide solution, and a titration curve as shown in FIG. 2 is obtained. If necessary, the measurement object may be subjected to a defibration treatment similar to the defibration treatment process described below. As shown in FIG. 2, in this neutralization titration, a single point is observed where the increment (the derivative of pH with respect to the amount of alkali added) is maximum on the curve plotting the measured pH against the amount of alkali added. This maximum increment is called the first end point. Here, the region from the start of titration to the first end point in FIG. 2 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used in the titration. The amount of alkali required in the first region of the titration curve (mmol) was divided by the solid content (g) in the fine fibrous cellulose-containing slurry to be titrated to calculate the amount of carboxyl groups introduced (mmol / g). The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) (hereinafter referred to as the amount of carboxy groups (acid type)) per gram of mass of fibrous cellulose.
[0047] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose with the cation C as the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) (mmol / g) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0048] In measuring the amount of substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of substituents may be lower than the actual amount, and an accurate value may not be obtained. For example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds as an appropriate amount of dropping and titration interval. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0049] The amount of sulfur oxoacid groups or sulfone groups introduced into fibrous cellulose can be calculated by freeze-drying a slurry containing fibrous cellulose, pulverizing the slurry, and measuring the amount of sulfur in the resulting pulverized sample. Specifically, a slurry containing fibrous cellulose is freeze-dried, and the resulting pulverized sample is subjected to pressurized heating decomposition with nitric acid in a closed container, and then appropriately diluted and the amount of sulfur is measured by ICP-OES. The amount of sulfur oxoacid groups or sulfone groups (unit: mmol / g) of fibrous cellulose is calculated by dividing the value by the bone dry mass of the fibrous cellulose used.
[0050] <<Method of manufacturing fine fibrous cellulose>> (cellulose-containing fiber materials) Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), and mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP). Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, but may be, for example, deinked pulp made from recycled paper. The pulp of this embodiment may be one of the above types alone or a mixture of two or more types. Among the above pulps, for example, wood pulp and deinked pulp are preferred from the viewpoint of availability. Furthermore, among wood pulps, for example, chemical pulp is more preferred, and kraft pulp and sulfite pulp are even more preferred, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of obtaining long-fiber fine fibrous cellulose with a large axial ratio due to little decomposition of cellulose in the pulp. Note that the viscosity tends to increase when long-fiber fine fibrous cellulose with a large axial ratio is used. As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Moreover, instead of fiber raw materials containing cellulose, fibers formed from linear nitrogen-containing polysaccharide polymers such as chitin and chitosan can also be used.
[0051] In order to obtain the fine fibrous cellulose having the ionic substituent introduced therein, it is preferable to have an ionic substituent introduction step for introducing an ionic substituent into the fiber raw material containing the above-mentioned cellulose, a washing step, an alkali treatment step (neutralization step), and a defibration treatment step in this order, and an acid treatment step may be included instead of or in addition to the washing step. Examples of the ionic substituent introduction step include a phosphorus oxo acid group introduction step, a carboxy group introduction step, a sulfur oxo acid group introduction step, a xanthate group introduction step, a phosphonic or phosphine group introduction step, a sulfonic group introduction step, and a cationic group introduction step. Each of these steps will be described below.
[0052] (Ionic Substituent Introduction Step) -Phosphorus oxo acid group introduction process- The phosphorus oxo acid group introduction step is a step in which at least one compound selected from compounds capable of introducing phosphorus oxo acid groups by reacting with hydroxyl groups in a fiber raw material containing cellulose (hereinafter also referred to as "compound A") is allowed to act on the fiber raw material containing cellulose, thereby obtaining a fiber into which phosphorus oxo acid groups have been introduced. In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B. An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B are each added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. In addition, compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0053] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be, for example, 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and may include, for example, pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates may include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphorus oxoacid groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium dihydrogen phosphate are more preferred. The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to 100 parts by mass of the fiber raw material (bone dry mass) is preferably 0.5 parts by mass or more and 100 parts by mass or less, more preferably 1 part by mass or more and 50 parts by mass or less, and even more preferably 2 parts by mass or more and 30 parts by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0054] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved. The amount of compound B added per 100 parts by mass (bone dry mass) of the fiber raw material is not particularly limited, but is preferably, for example, 1 part by mass or more and 500 parts by mass or less, more preferably 10 parts by mass or more and 400 parts by mass or less, and even more preferably 100 parts by mass or more and 350 parts by mass or less.
[0055] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0056] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0057] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation and then heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A). In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, to the outside of the device system, the moisture held by the slurry and the moisture generated by the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio. The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1,000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0058] The amount of phosphorus oxoacid groups introduced into the fiber raw material is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxoacid groups introduced into the fiber raw material is preferably 5.20 mmol / g or less per 1 g (mass) of fine fibrous cellulose, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of phosphorus oxoacid groups introduced within the above range, it is possible to easily fine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0059] -Carboxy group introduction process- The carboxyl group introduction process is carried out by subjecting a fiber raw material containing cellulose to an oxidation process such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or by treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride or a derivative thereof of a compound having a carboxylic acid-derived group. Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0060] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0061] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of a pH of 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). Furthermore, by adding sodium chlorite, the aldehyde generated during the oxidation process can be efficiently oxidized to a carboxyl group. The TEMPO oxidation treatment may be carried out under conditions of a pH of 10 to 11. This type of treatment is also called alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be carried out, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a co-catalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material. The amount of carboxyl groups introduced into the fiber raw material varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, it is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. Also, it is preferably 3.65 mmol / g or less, more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.20 mmol / g or less, and particularly preferably 2.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, it may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose. By setting the amount of carboxyl groups introduced within the above range, it is possible to facilitate the fine pulverization of cellulose fibers in the fine pulverization treatment step and to increase the stability of the fine fibrous cellulose.
[0062] -Sulfur oxo acid group introduction process- The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).
[0063] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may be neutralized to various degrees. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0064] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treating temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treating temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treating temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0065] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0066] The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 0.05 mmol / g or more, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 5.00 mmol / g or less, more preferably 3.00 mmol / g or less. By setting the amount of sulfur oxoacid groups introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose.
[0067] -Oxidation process using a chlorine-based oxidizing agent (second carboxyl group introduction process)- The ionic substituent introduction step may include an oxidation step using a chlorine-based oxidizing agent, in which the chlorine-based oxidizing agent is added to a wet or dry fiber raw material having a hydroxyl group to cause a reaction, thereby introducing a carboxyl group into the fiber raw material.
[0068] Examples of chlorine-based oxidizing agents include hypochlorous acid, hypochlorites, chlorous acid, chlorites, chloric acid, chlorates, perchloric acid, perchlorates, and chlorine dioxide. In terms of the efficiency of introducing a substituent, and therefore the efficiency of defibration, cost, and ease of handling, the chlorine-based oxidizing agent is preferably sodium hypochlorite, sodium chlorite, or chlorine dioxide. When adding a chlorine-based oxidizing agent, it may be added to the fiber raw material as it is as a reagent (solid or liquid), or it may be added after dissolving in an appropriate solvent.
[0069] The concentration of the chlorine-based oxidizing agent in the solution in the oxidation step using the chlorine-based oxidizing agent is, for example, preferably 1% by mass to 1,000% by mass, more preferably 5% by mass to 500% by mass, and even more preferably 10% by mass to 100% by mass. The amount of the chlorine-based oxidizing agent added per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 10 parts by mass to 10,000 parts by mass, and even more preferably 100 parts by mass to 5,000 parts by mass.
[0070] The reaction time with the chlorine-based oxidizing agent in the oxidation step using the chlorine-based oxidizing agent may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. The pH during the reaction is preferably from 5 to 15, more preferably from 7 to 14, and even more preferably from 9 to 13. At the start of the reaction, the pH during the reaction is preferably kept constant (for example, pH 11) by appropriately adding hydrochloric acid or sodium hydroxide. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0071] -Xanthate group introduction process (xanthogen acid esterification process)- The ionic substituent introduction step may include, for example, a xanthate group introduction step (hereinafter also referred to as a xanthate formation step). In the xanthate formation step, carbon disulfide and an alkali compound are added to a wet or dry fiber raw material having a hydroxyl group to react with each other, thereby introducing a xanthate group into the fiber raw material. Specifically, carbon disulfide is added to a fiber raw material that has been converted into alkali cellulose by the method described below, and the reaction is carried out.
[0072] ((Alkaline cellulose)) When introducing an ionic substituent into a fiber raw material, it is preferable to make the cellulose contained in the fiber raw material into an alkali cellulose by applying an alkali solution to the cellulose. This treatment causes some of the hydroxyl groups of the cellulose to be ionized, thereby increasing the nucleophilicity (reactivity). The alkali compound contained in the alkali solution is not particularly limited, and may be an inorganic alkali compound or an organic alkali compound. For example, sodium hydroxide, potassium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide are preferably used because of their high versatility. The alkali cellulose may be made into an alkali cellulose simultaneously with the introduction of an ionic substituent, before the introduction, or at both the same timing.
[0073] The solution temperature at the start of alkali cellulose formation is preferably 0°C or higher and 50°C or lower, more preferably 5°C or higher and 40°C or lower, and even more preferably 10°C or higher and 30°C or lower.
[0074] The alkali concentration in the alkali solution is preferably 0.01 mol / L to 4 mol / L in terms of molar concentration, more preferably 0.1 mol / L to 3 mol / L inclusive, and even more preferably 1 mol / L to 2.5 mol / L inclusive. In particular, when the treatment temperature in the alkali cellulose formation is less than 10° C., the alkali concentration is preferably 1 mol / L to 2 mol / L inclusive.
[0075] The treatment time for alkali cellulose formation is preferably 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more, and the alkali treatment time is preferably 6 hours or less, more preferably 5 hours or less, and even more preferably 4 hours or less.
[0076] By adjusting the type of alkaline solution, treatment temperature, concentration, and immersion time as described above, it is possible to suppress the penetration of the alkaline solution into the crystalline regions of cellulose, making it easier to maintain the crystal structure of cellulose type I, and increasing the yield of fine fibrous cellulose.
[0077] When the introduction of ionic substituents and the conversion to alkali cellulose are not carried out simultaneously, the conversion to alkali cellulose is preferably carried out before the introduction of ionic substituents. In this case, the alkali cellulose obtained by the conversion to alkali cellulose is preferably subjected to solid-liquid separation and water removal by a general deliquation method such as centrifugation or filtration. This improves the reaction efficiency in the subsequent ionic substituent introduction step. The cellulose fiber concentration after solid-liquid separation is preferably 5% to 50%, more preferably 10% to 40%, and even more preferably 15% to 35%.
[0078] -Phosphonic or phosphine group introduction step (phosphoalkylation step)- The ionic substituent introduction step may include a phosphonic or phosphine group introduction step (phosphoalkylation step). In the phosphoalkylation step, a compound having a reactive group and a phosphonic or phosphine group (compound E A ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a phosphonic or phosphine group into the fiber raw material.
[0079] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E A Examples of the compound include vinyl phosphonic acid, phenyl vinyl phosphonic acid, and phenyl vinyl phosphinic acid. From the viewpoints of the efficiency of introducing the substituent, the defibration efficiency, the cost, and the ease of handling, compound E A is preferably vinylphosphonic acid. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0080] Compound E A When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0081] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0082] Compound E A The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0083] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0084] -Sulfonic group introduction step (sulfoalkylation step)- The ionic substituent introduction step may include a sulfone group introduction step (sulfoalkylation step). In the sulfoalkylation, a compound having a reactive group and a sulfone group (compound E) is used as an essential component. B ) and, as an optional component, an alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a sulfone group into the fiber raw material.
[0085] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E B Examples of suitable sulfonates include sodium 2-chloroethanesulfonate, sodium vinylsulfonate, sodium p-styrenesulfonate, and 2-acrylamido-2-methylpropanesulfonic acid. Among these, compound E is particularly preferred in terms of the efficiency of introducing substituents, and therefore the defibration efficiency, cost, and ease of handling. B is preferably sodium vinyl sulfonate. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0086] Compound E B When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0087] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0088] Compound E BThe amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0089] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 15 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0090] -Carboxyalkylation step (third carboxy group introduction step)- The ionic substituent introduction step may include a carboxyalkylation step. As an essential component, a compound having a reactive group and a carboxy group (compound E C ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0091] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E C As the chloropropionic acid, monochloroacetic acid, sodium monochloroacetate, 2-chloropropionic acid, 3-chloropropionic acid, sodium 2-chloropropionate, and sodium 3-chloropropionate are preferred from the standpoint of efficiency of introducing substituents, and therefore defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0092] Compound E CWhen adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0093] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0094] Compound E C The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0095] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 3 minutes to 500 minutes, and even more preferably from 5 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0096] -Cationic group introduction step (cationization step)- As an essential component, a compound having a reactive group and a cationic group (compound E D ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a cationic group into the fiber raw material.
[0097] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Examples of the cationic group include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group. Compound E D As the alkyl group, glycidyl trimethyl ammonium chloride, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride, etc. are preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner. The amount of addition is also preferably as described above.
[0098] Compound E D When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0099] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0100] Compound E D The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0101] The reaction time may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 5 minutes to 500 minutes, and even more preferably from 10 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0102] (Cleaning process) In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0103] (Alkaline treatment (neutralization) process) When producing fine fibrous cellulose, an alkali treatment (neutralization treatment) may be performed on the fiber raw material between the ionic substituent introduction step and the defibration treatment step described below. The alkali treatment method is not particularly limited, but may be, for example, a method of immersing the ionic substituent-introduced fiber in an alkali solution. The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility. The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The time for immersing the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the bone dry mass of the ionic substituent-introduced fiber.
[0104] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0105] (Acid treatment process) When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described below. For example, the steps of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order. The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid. The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the bone dry mass of the fiber raw material.
[0106] (Fibrillation process) By subjecting the ionic substituent-introduced fibers to a defibration treatment in a defibration treatment step, fine fibrous cellulose can be obtained. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0107] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0108] The solids concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. Furthermore, the slurry obtained by dispersing the phosphorus oxo acid group-introduced fiber in a dispersion medium may contain solid matters other than the phosphorus oxo acid group-introduced fiber, such as urea having hydrogen bonding properties.
[0109] (Nitrogen removal treatment) The process for producing fine fibrous cellulose may further include a step of reducing the amount of nitrogen (nitrogen removal process). By reducing the amount of nitrogen, fine fibrous cellulose that can be further suppressed from being discolored can be obtained. The nitrogen removal process is preferably carried out before the defibration process.
[0110] In the nitrogen removal treatment step, it is preferable to adjust the pH of the slurry containing the substituent-introduced fiber to 10 or more and perform a heat treatment. In the heat treatment, the liquid temperature of the slurry is preferably 50° C. or more and 100° C. or less, and the heating time is preferably 15 minutes or more and 180 minutes or less. When adjusting the pH of the slurry containing the substituent-introduced fiber, it is preferable to add an alkali compound that can be used in the above-mentioned alkali treatment step to the slurry.
[0111] After the nitrogen removal treatment step, the fiber having ionic substituents introduced therein may be subjected to a washing step, if necessary. The washing step is carried out, for example, by washing the fiber having ionic substituents introduced therein with water or an organic solvent. The number of washing steps carried out in each washing step is not particularly limited.
[0112] (Substituent removal treatment) The method for producing fine fibrous cellulose may include a step of removing at least a part of the substituent from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. By going through such a step, it is possible to obtain fine fibrous cellulose having a small amount of substituents introduced but a small fiber width. In this specification, the step of removing at least a part of the substituent from fine fibrous cellulose is also referred to as a substituent removal treatment step.
[0113] Examples of the substituent removal treatment step include a step of heat treating, enzyme treating, acid treating, alkali treating, etc., fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. These may be performed alone or in combination. Among them, the substituent removal treatment step is preferably a heat treating step or an enzyme treating step. By passing through the above treatment steps, at least a part of the substituent is removed from the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and a fine fibrous cellulose having an introduction amount of less than 0.5 mmol / g can be obtained. By forming a fine fibrous cellulose-containing layer using such fine fibrous cellulose, a laminate having better water resistance can be obtained.
[0114] The substituent removal treatment step is preferably carried out in the form of a slurry. That is, the substituent removal treatment step is preferably a step of subjecting a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less to a heat treatment, an enzyme treatment, an acid treatment, an alkali treatment, or the like. By carrying out the substituent removal treatment step in the form of a slurry, it is possible to prevent the residue of colored substances generated by heating or the like during the substituent removal treatment, and added or generated acids, alkalis, salts, and the like. This makes it possible to suppress coloring of the fine fibrous cellulose-containing layer. In addition, when a treatment is carried out to remove salts derived from the substituents removed after the substituent removal treatment, it is also possible to increase the efficiency of salt removal.
[0115] When a substitution removal treatment is performed on a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the concentration of the fine fibrous cellulose in the slurry is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. The concentration of the fine fibrous cellulose in the slurry is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. By setting the concentration of the fine fibrous cellulose in the slurry within the above range, the substitution removal treatment can be performed more efficiently. Furthermore, by setting the concentration of the fine fibrous cellulose in the slurry within the above range, it is possible to prevent the coloring substances generated by heating during the substitution removal treatment, and the residue of acids, alkalis, salts, etc. that are added or generated. This makes it possible to suppress the coloring of the fine fibrous cellulose-containing layer. In addition, when performing a treatment to remove salts derived from the substituents removed after the substitution removal treatment, it is also possible to increase the efficiency of removing the salts.
[0116] When the substituent removal treatment step is a step of heat treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the heating temperature in the heat treatment step is preferably 40° C. or more, more preferably 50° C. or more, and even more preferably 60° C. or more. The heating temperature in the heat treatment step is preferably 250° C. or less, more preferably 230° C. or less, and even more preferably 200° C. or less. In particular, when the substituent of the fine fibrous cellulose to be subjected to the substituent removal treatment step is a phosphorus oxo acid group, the heating temperature in the heat treatment step is preferably 80° C. or more, more preferably 100° C. or more, and even more preferably 120° C. or more.
[0117] When the substituent removal treatment step is a step of heat treatment, the heating device that can be used in the heat treatment step is not particularly limited, but a hot air heating device, a steam heating device, an electric heating device, a hydrothermal heating device, a thermal heating device, an infrared heating device, a far-infrared heating device, a microwave heating device, a high-frequency heating device, a stirring dryer, a rotary dryer, a disk dryer, a roll-type heating device, a plate-type heating device, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, and a reduced pressure dryer can be used. From the viewpoint of preventing evaporation, it is preferable that the heating is performed in a closed system, and from the viewpoint of further increasing the heating temperature, it is preferable that the heating is performed in a pressure-resistant device or container. The heating treatment may be a batch treatment, a batch continuous treatment, or a continuous treatment.
[0118] When the substituent removal treatment step is a step of enzymatically treating fine fibrous cellulose having substituents and a fiber width of 1000 nm or less, it is preferable to use a phosphate ester hydrolase, a sulfate ester hydrolase, or the like in the enzymatic treatment step depending on the type of substituent.
[0119] In the enzyme treatment step, the enzyme is preferably added so that the enzyme activity is 0.1 nkat or more per 1 g of fine fibrous cellulose, more preferably 1.0 nkat or more, and even more preferably 10 nkat or more. The enzyme is preferably added so that the enzyme activity is 100,000 nkat or less per 1 g of fine fibrous cellulose, more preferably 50,000 nkat or less, and even more preferably 10,000 nkat or less. After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferable to perform a treatment under conditions of 0°C or more and less than 50°C for 1 minute to 100 hours.
[0120] After the enzyme reaction, a step of inactivating the enzyme may be performed. Examples of the method of inactivating the enzyme include a method of inactivating the enzyme by adding an acid component or an alkali component to the slurry that has been subjected to the enzyme treatment, and a method of inactivating the enzyme by raising the temperature of the slurry that has been subjected to the enzyme treatment to 90° C. or higher.
[0121] When the substituent removal treatment step is a step of acid-treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, it is preferable to add an acid compound that can be used in the acid treatment step described above to the slurry in the acid treatment step.
[0122] When the substituent removal treatment step is a step of subjecting fine fibrous cellulose having a substituent and having a fiber width of 1000 nm or less to an alkali treatment, it is preferable to add an alkali compound that can be used in the alkali treatment step described above to the slurry in the alkali treatment step.
[0123] In the substituent removal treatment step, it is preferable that the substituent removal reaction proceeds uniformly. In order to proceed with the reaction uniformly, for example, the slurry containing the fine fibrous cellulose may be stirred, or the specific surface area of the slurry may be increased. As a method for stirring the slurry, an external mechanical shear may be applied, or the self-stirring may be promoted by increasing the liquid feed rate of the slurry during the reaction.
[0124] In the substituent removal treatment step, a spacer molecule may be added. The spacer molecule enters between adjacent fine fibrous cellulose particles, thereby acting as a spacer for providing a fine space between the fine fibrous cellulose particles. By adding such a spacer molecule in the substituent removal treatment step, the aggregation of the fine fibrous cellulose particles after the substituent removal treatment can be suppressed. This makes it possible to more effectively increase the transparency of the fine fibrous cellulose-containing layer.
[0125] The spacer molecule is preferably a water-soluble organic compound. Examples of the water-soluble organic compound include sugar, water-soluble polymer, and urea. Specific examples include trehalose, urea, polyethylene glycol (PEG), polyethylene oxide (PEO), carboxymethyl cellulose, and polyvinyl alcohol (PVA). In addition, water-soluble organic compounds that can be used include alkyl methacrylate-acrylic acid copolymers, polyvinylpyrrolidone, sodium polyacrylate, propylene glycol, dipropylene glycol, polypropylene glycol, isoprene glycol, hexylene glycol, 1,3-butylene glycol, polyacrylamide, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, alginic acid, pullulan, carrageenan, pectin, cationic starch, raw starch, oxidized starch, etherified starch, esterified starch, amylose and other starches, glycerin, diglycerin, polyglycerin, hyaluronic acid, and metal salts of hyaluronic acid.
[0126] Also, known pigments can be used as spacer molecules, such as kaolin (containing clay), calcium carbonate, titanium oxide, zinc oxide, amorphous silica (containing colloidal silica), aluminum oxide, zeolite, sepiolite, smectite, synthetic smectite, magnesium silicate, magnesium carbonate, magnesium oxide, diatomaceous earth, styrene-based plastic pigments, hydrotalcite, urea resin-based plastic pigments, and benzoguanamine-based plastic pigments.
[0127] (pH adjustment process) When the above-mentioned substituent removal treatment step is carried out in the form of a slurry, a step of adjusting the pH of the slurry containing the fine fibrous cellulose may be provided before the substituent removal treatment step. For example, an ionic substituent is introduced into the cellulose fiber, and the counter ion of the ionic substituent is Na + In this case, the slurry containing the defibrated fine fibrous cellulose exhibits weak alkalinity. If heating is performed in this state, monosaccharides, which are one of the causes of coloring, may be generated due to decomposition of the cellulose, so it is preferable to adjust the pH of the slurry to 8 or less. Similarly, monosaccharides may be generated under acidic conditions, so it is preferable to adjust the pH of the slurry to 3 or more.
[0128] In addition, when the fine fibrous cellulose having a substituent is a fine fibrous cellulose having a phosphate group, from the viewpoint of improving the efficiency of removing the substituent, it is preferable that the phosphorus of the phosphate group is in a state that is easily susceptible to nucleophilic attack. The phosphorus that is easily susceptible to nucleophilic attack is cellulose-OP(=O)(-OH + )(-O-Na + ) is a state of neutralization level 1, and to achieve this state, The pH of the slurry is preferably adjusted to 3 or more and 8 or less, and more preferably adjusted to 4 or more and 6 or less.
[0129] The means for adjusting the pH is not particularly limited, and for example, an acid component or an alkali component may be added to the slurry containing the fine fibrous cellulose. The acid component may be either an inorganic acid or an organic acid, and examples of the inorganic acid include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the organic acid include formic acid, acetic acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, maleic acid, succinic acid, tartaric acid, fumaric acid, and gluconic acid. The alkali component may be an inorganic alkali compound or an organic alkali compound. Examples of the inorganic alkali compound include lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, lithium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, sodium carbonate, and sodium hydrogen carbonate. Examples of the organic alkali compound include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, and N,N-dimethyl-4-aminopyridine.
[0130] In addition, in the pH adjustment step, an ion exchange treatment may be performed to adjust the pH. In the ion exchange treatment, a strong acid cation exchange resin or a weak acid ion exchange resin may be used. By treating with an appropriate amount of cation exchange resin for a sufficient time, a slurry containing fine fibrous cellulose with a desired pH can be obtained. Furthermore, in the pH adjustment step, the addition of an acid component or an alkali component may be combined with the ion exchange treatment.
[0131] (Salt removal process) After the substituent removal treatment step, it is preferable to carry out a treatment for removing salts derived from the removed substituents. By removing the salts derived from the substituents, it becomes easier to obtain fine fibrous cellulose capable of suppressing coloration. The means for removing the salts derived from the substituents is not particularly limited, and examples thereof include a washing treatment and an ion exchange treatment. The washing treatment is carried out by washing the fine fibrous cellulose aggregated in the substituent removal treatment with, for example, water or an organic solvent. In the ion exchange treatment, an ion exchange resin can be used.
[0132] (Uniform dispersion processing) The substituent removal treatment step may be followed by a step of uniformly dispersing the fine fibrous cellulose obtained through the substituent removal treatment. By subjecting the fine fibrous cellulose to the substituent removal treatment, at least a portion of the fine fibrous cellulose is aggregated. The uniform dispersion treatment step is a step of uniformly dispersing the fine fibrous cellulose thus aggregated.
[0133] In the uniform dispersion treatment step, for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a twin-shaft kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser or a beater can be used. Among the above uniform dispersion treatment devices, it is more preferable to use a high-speed defibrator or a high-pressure homogenizer.
[0134] The treatment conditions in the uniform dispersion treatment step are not particularly limited, but it is preferable to increase the maximum movement speed of the fine fibrous cellulose during treatment and the pressure during treatment. In the case of a high-speed defibrator, the peripheral speed is preferably 20 m / sec or more, more preferably 25 m / sec or more, and even more preferably 30 m / sec or more. A high-pressure homogenizer is more preferably used because it has a higher maximum movement speed of the fine fibrous cellulose during treatment and a higher pressure during treatment than a high-speed defibrator. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 1 MPa or more and 350 MPa or less, more preferably 10 MPa or more and 300 MPa or less, and even more preferably 50 MPa or more and 250 MPa or less.
[0135] In the uniform dispersion treatment step, the above-mentioned spacer molecules may be added. By adding such spacer molecules in the uniform dispersion treatment step, the fine fibrous cellulose can be uniformly dispersed more smoothly. This makes it possible to more effectively increase the transparency of the fine fibrous cellulose-containing layer.
[0136] In the fine fibrous cellulose-containing layer in this embodiment, the content of fine fibrous cellulose in the solid content of the fine fibrous cellulose-containing layer is, from the viewpoint of improving the rigidity of the laminate, preferably 30% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, still more preferably 65% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, still more preferably 75% by mass or less. As the fine fibrous cellulose, a fine fibrous cellulose containing an ionic group and an unmodified fine fibrous cellulose may be used in combination.
[0137] <Hydrophilic polymer> In the present embodiment, the fine fibrous cellulose-containing layer preferably contains a hydrophilic polymer from the viewpoint of ease of manufacturing the fine fibrous cellulose-containing layer. The hydrophilic polymer generally refers to a polymer compound that is easily dissolved, swollen, or wetted by water. Examples of the hydrophilic polymer include a polymer compound having an ionic group such as a carboxy group, a sulfone group, or an amino group in the molecular structure, and a polymer compound having a non-ionic hydrophilic group such as a hydroxyl group, an amide group, an ether group, or a polyoxyethylene group or a polyoxypropylene group. Examples of hydrophilic polymers include carboxyvinyl polymers, polyvinyl alcohol, alkyl methacrylate-acrylic acid copolymers, polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates such as sodium polyacrylate, alkyl acrylate copolymers, urethane copolymers, modified polyesters, modified polyimides, polyalkylene glycols such as polyethylene glycol, polyethylene oxide, and polypropylene glycol, polycations such as polyacrylamide and polyethyleneimine, polyanions, amphoteric polymers, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, and chrysanthemum gum. Examples of the thickening polysaccharides include inseed, alginic acid, metal salts of alginic acid, pullulan, sacran, and pectin; cellulose derivatives include carboxymethylcellulose, carboxyethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and hydroxyethylcellulose; starches include cationic starch, raw starch, oxidized starch, etherified starch, esterified starch, dextrin, and amylose; glycerins such as polyglycerin; hyaluronic acid, metal salts of hyaluronic acid; proteins such as casein, etc. Also, copolymers of these hydrophilic polymers may be used. Among these, polyvinyl alcohol, polyalkylene glycol, and cellulose derivatives are preferred, cellulose derivatives are more preferred, and hydroxypropylmethylcellulose is even more preferred.
[0138] In the fine fibrous cellulose-containing layer in this embodiment, the content of the hydrophilic polymer is, from the viewpoint of improving the rigidity of the laminate, preferably 90 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 45 parts by mass or less, and preferably 10 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 30 parts by mass or more, and even more preferably 40 parts by mass or more, per 100 parts by mass of the fine fibrous cellulose.
[0139] In the fine fibrous cellulose-containing layer in this embodiment, the sum of the content of fine fibrous cellulose and the content of hydrophilic polymer in the solid content of the fine fibrous cellulose-containing layer is, from the viewpoint of improving the rigidity of the laminate, preferably 80 mass% or more, more preferably 85 mass% or more, even more preferably 90 mass% or more, and even more preferably 95 mass% or more, and 100 mass% or less.
[0140] In the laminate of this embodiment, the "fine fibrous cellulose-containing layer content (%)" (100 x sum of thicknesses of fine fibrous cellulose-containing layers 1 and 2 (μm) / thickness of laminate (μm)) is, from the viewpoint of improving the rigidity of the laminate, preferably 16.0% or less, more preferably 14.0% or less, even more preferably 12.0% or less, still more preferably 10.0% or less, and is preferably 0.6% or more, more preferably 0.9% or more, even more preferably 1.2% or more, and still more preferably 1.5% or more.
[0141] <Other ingredients> The fine fibrous cellulose-containing layer 1 in this embodiment may contain components (other components) other than the fine fibrous cellulose having a fiber width of 1,000 nm or less and the hydrophilic polymer. Examples of the other components include fibrous cellulose having a fiber width of more than 1,000 nm, hydrophilic low-molecular weight compounds, paper strength agents, thermoplastic resins, surfactants, organic ions, coupling agents, inorganic layered compounds, inorganic compounds, leveling agents, preservatives, defoamers, organic particles, lubricants, antistatic agents, UV protection agents, dyes, pigments, stabilizers, magnetic powders, alignment promoters, plasticizers, dispersants, color inhibitors, polymerization inhibitors, pH adjusters, and crosslinking agents. In the fine fibrous cellulose-containing layer 1 in this embodiment, the total content of "other components" in the solid content of the fine fibrous cellulose-containing layer can be, for example, 5 mass% or less, or 3 mass% or less, or 1 mass% or less, or even 0 mass%. Regarding <other components>, the fine fibrous cellulose-containing layer 2 in this embodiment is the same as the fine fibrous cellulose-containing layer 1 in this embodiment.
[0142] <Thickness> The thickness of the fine fibrous cellulose-containing layer 1 in this embodiment is preferably 20 μm or more, more preferably 25 μm or more, even more preferably 30 μm or more, and is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less. The preferred range of the thickness of the fine fibrous cellulose-containing layer 2 in this embodiment is the same as the above-mentioned thickness range. The thickness of the fine fibrous cellulose-containing layer is preferably adjusted appropriately depending on the application of the laminate.
[0143] <Basic weight> The basis weight of the fine fibrous cellulose-containing layer in this embodiment is preferably 25 g / m 2 More preferably, 30 g / m 2 More preferably, 35 g / m 2 and preferably 400 g / m 2 Less than 300 g / m2 Less than 230 g / m 2 The preferred range of the basis weight of the fine fibrous cellulose-containing layer 2 in this embodiment is the same as the above-mentioned range of basis weight. The basis weight of the fine fibrous cellulose-containing layer is preferably adjusted appropriately depending on the application of the laminate.
[0144] <density> The density of the fine fibrous cellulose-containing layer 1 in this embodiment is preferably 0.6 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3 and preferably 2.1 g / cm 3 Less than or equal to 1.8 g / cm 3 More preferably, 1.5 g / cm 3 The preferred range of the density of the fine fibrous cellulose-containing layer 2 in this embodiment is the same as the above-mentioned density range. The density of the fine fibrous cellulose-containing layer is calculated by dividing the basis weight of the fine fibrous cellulose-containing layer by the thickness.
[0145] [Resin films 1 and 2] As described above, the laminate of this embodiment has the resin film 1 on one surface of the core resin plate, and the resin film 2 on the other surface of the core resin plate. The components contained or may be contained in the resin film 1, and the thickness of the resin film 1 may be the same as or different from the components contained or may be contained in the resin film 2, and the thickness of the resin film 2, but are preferably the same. Hereinafter, resin films 1 and 2 will be collectively referred to simply as "resin films".
[0146] The resin constituting the resin film is not particularly limited as long as it can produce a resin film having a tensile modulus greater than the tensile modulus of the core resin plate, but it preferably contains at least one selected from the group consisting of polyethylene terephthalate and polymethyl methacrylate, and it is more preferable that it contains polyethylene terephthalate.
[0147] <Thickness> The thickness of the resin film 1 in this embodiment is preferably 30 μm or more, more preferably 80 μm or more, even more preferably 130 μm or more, still more preferably 180 μm or more, particularly preferably 220 μm or more, and is preferably 500 μm or less, more preferably 450 μm or less, even more preferably 400 μm or less, still more preferably 350 μm or less, particularly preferably 300 μm or less. The preferred range of the thickness of the resin film 2 in this embodiment is the same as the above-mentioned thickness range. The thickness of the resin film is preferably adjusted appropriately depending on the application of the laminate.
[0148] <Tensile modulus> The tensile modulus of the resin film 1 in this embodiment is preferably 1.5 GPa or more, more preferably 2.0 GPa or more, and even more preferably 2.5 GPa or more from the viewpoint of improving the rigidity of the laminate, and is preferably 5.5 GPa or less, more preferably 5.0 GPa or less, and even more preferably 4.5 GPa or less from the viewpoint of ease of manufacture of the laminate. The preferred range of the tensile modulus of the resin film 2 in this embodiment is the same as the range of the tensile modulus described above. The tensile modulus of the resin film in this embodiment is a value obtained in accordance with JIS K 7127:1999. The test piece used for the tensile modulus can be obtained by cutting from the raw resin film or the resin film in the laminate. In addition, the polymer constituting the resin film in the laminate may be identified by spectral analysis such as infrared absorption spectroscopy, and the polymer may be used to prepare a test piece having the same thickness as the resin film in the laminate.
[0149] [Laminate properties] [Total light transmittance] The total light transmittance of the laminate of this embodiment is preferably 80% or more, more preferably 83% or more, and even more preferably 85% or more. Meanwhile, the upper limit of the total light transmittance of the laminate may be, for example, 100%. The total light transmittance of the laminate can be controlled by the fiber width of the fine fibrous cellulose, the type of ionic group, the amount of ionic group introduced, the type of hydrophilic polymer, the type of resin constituting the resin film, the content of the fine fibrous cellulose and the hydrophilic polymer in the fine fibrous cellulose-containing layer, the thickness of each layer constituting the laminate, and the like. The total light transmittance of the laminate is a value measured in accordance with JIS K 7361-1:1997.
[0150] [Haze] The haze of the laminate of this embodiment is preferably 6.0% or less, more preferably 5.5% or less, even more preferably 5.0% or less, and even more preferably 4.5% or less. On the other hand, the lower limit of the haze of the laminate may be, for example, 0%. The haze of the laminate can be controlled by the fiber width of the fine fibrous cellulose, the type of ionic group, the amount of ionic group introduced, the type of hydrophilic polymer, the type of resin constituting the resin film, the content of the fine fibrous cellulose and the hydrophilic polymer in the fine fibrous cellulose-containing layer, the thickness of each layer constituting the laminate, etc. The haze of the laminate is a value measured in accordance with JIS K 7136:2000.
[0151] [Yellow Index] The yellow index (YI value) of the laminate of this embodiment is preferably 7.5 or less, more preferably 7.0 or less, even more preferably 6.5 or less, and even more preferably 6.0 or less, with no particular lower limit. If the YI value before and after heating is within the above range, yellowing due to heating is suppressed, which is preferable. The YI value of the laminate can be controlled by the fiber width of the fine fibrous cellulose, the type of ionic group, the amount of ionic group introduced, the type of hydrophilic polymer, the type of resin constituting the resin film, the content of fine fibrous cellulose and hydrophilic polymer in the fine fibrous cellulose-containing layer, the thickness of each layer constituting the laminate, etc. The YI value of the laminate is a value measured in accordance with JIS K 7373:2006.
[0152] [Bending strength] The laminate of the present embodiment preferably has a high bending strength, and the laminate having a high bending strength is preferable because it has excellent rigidity. The bending strength of the laminate is preferably 90 MPa or more, more preferably 95 MPa or more, and even more preferably 100 MPa or more. The upper limit is not particularly limited, but from the viewpoint of ease of production, it is preferably 150 MPa or less. The bending strength of the laminate can be controlled by the thickness of the core resin plate, the basis weight and thickness of the fiber width of the fine fibrous cellulose, the type of resin constituting the resin film, the thickness of the resin film, etc. The bending strength of the laminate is a value measured in accordance with JIS K 7171:2016.
[0153] [Flexural modulus] The laminate of the present embodiment preferably has a high flexural modulus, and the laminate having a high flexural modulus is preferable because it has excellent rigidity. The flexural modulus of the laminate is preferably 2.5 GPa or more, more preferably 3.0 GPa or more, and even more preferably 3.4 GPa or more. The upper limit is not particularly limited, but is preferably 6.0 GPa or less from the viewpoint of ease of manufacture. The flexural modulus of the laminate can be controlled by the thickness of the core resin plate, the basis weight and thickness of the fiber width of the fine fibrous cellulose, the type of resin constituting the resin film, the thickness of the resin film, etc. The flexural modulus of the laminate is a value measured in accordance with JIS K 7171:2016.
[0154] [Coefficient of linear thermal expansion] The laminate of this embodiment preferably has a linear thermal expansion coefficient at 25 to 110° C. of 70 ppm / K or less. The linear thermal expansion coefficient is preferably low, but from the viewpoint of production, it is more preferably 55 ppm / K or less, even more preferably 50 ppm / K or less, even more preferably 45 ppm / K or less, and particularly preferably 40 ppm / K or less. The lower limit of the linear thermal expansion coefficient is not particularly limited, and may be, for example, 0 ppm / K. The linear thermal expansion coefficient of the laminate at 25 to 110°C can be controlled by the fiber width of the fine fibrous cellulose, the type of ionic group, the amount of ionic group introduced, the type of hydrophilic polymer, the type of resin constituting the resin film, the content of the fine fibrous cellulose and the hydrophilic polymer in the fine fibrous cellulose-containing layer, the thickness of each layer constituting the laminate, etc. The linear thermal expansion coefficient of the laminate at 25 to 110° C. is a value measured by the method described in the examples.
[0155] [Thickness] The thickness of the laminate of this embodiment is preferably 1,000 μm or more, more preferably 2,000 μm or more, and even more preferably 3,000 μm or more, and is preferably 6,000 μm or less, more preferably 5,000 μm or less, and even more preferably 4,000 μm or less. It is preferable that the thickness of the laminate is appropriately adjusted depending on the application.
[0156] [Method of manufacturing laminate] The laminate of this embodiment can be produced, for example, by carrying out "production of sheet 1," "production of sheet 2," and "formation of laminate." An example of a method for producing the laminate of this embodiment will be described below.
[0157] [Preparation of Sheet 1] A resin coating liquid (adhesive composition) is applied to the resin film 1 and dried at 65 to 85° C. for 1 to 15 minutes, thereby forming an adhesive layer 1B on the resin film 1. A mixed liquid containing fine fibrous cellulose, a hydrophilic polymer and water is applied onto the adhesive layer 1B, dried at 65 to 85°C for 30 to 90 minutes, and then aging treatment is performed at 85 to 95°C for 5 to 10 hours to develop the desired adhesive strength, thereby forming a fine fibrous cellulose-containing layer 1 on the adhesive layer 1B. The solid content of the mixture is, for example, 0.5 to 5.0% by mass. A resin coating liquid (adhesive composition) is applied onto the fine fibrous cellulose-containing layer 1, dried at 65 to 85°C for 1 to 15 minutes, and then aging treatment is performed at 85 to 95°C for 5 to 10 hours to develop the desired adhesive strength, thereby obtaining sheet 1 (layer structure: adhesive layer 1A-fine fibrous cellulose-containing layer 1-adhesive layer 1B-resin film 1).
[0158] [Preparation of Sheet 2] A resin coating liquid (the above-mentioned adhesive composition) is applied to a resin film 2 and dried at 65 to 85° C. for 1 to 15 minutes to form a sheet 2 (layer structure: adhesive layer-resin film 2).
[0159] [Formation of Laminate] Sheet 1 is placed on one side of the core resin plate so that the core resin plate and adhesive layer 1A are in contact with each other. Sheet 2 is placed on the other side of the core resin plate so that the core resin plate and adhesive layer are in contact with each other. The laminate precursor thus obtained is heated from room temperature (e.g., 23°C) to 130-190°C over 15-90 seconds while being pressurized at 1-10 MPa, and then held at this temperature for 15-90 seconds, and then cooled to 20-40°C over 15-90 seconds to obtain the laminate of this embodiment.
[0160] In the above [Preparation of Sheet 2], the sheet 2 (layer structure: adhesive layer 2A-fine fibrous cellulose-containing layer 2-adhesive layer 2B-resin film 2) can be obtained in the same manner as in the above [Preparation of Sheet 1]. In the above [Formation of Laminate], the sheet 2 is arranged so that the core resin plate and the adhesive layer 2A are in contact with each other, and the preferred laminate of this embodiment can be obtained in the same manner as in the above [Formation of Laminate].
[0161] The laminate of the present embodiment is suitable for optical components such as various display devices and various solar cells, etc. It is also suitable for applications such as substrates for electronic devices, separators for electrochemical elements, components for home appliances, window materials for various vehicles and buildings, interior materials, exterior materials, and packaging materials. EXAMPLES
[0162] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. Unless otherwise specified, the following operations were performed at room temperature (23°C) and a relative humidity of 50%.
[0163] <Production Example 1> (Phosphorylation) As the raw pulp, hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd. was used. This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 250 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0164] (Cleaning process) The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0165] (Neutralization treatment) Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.
[0166] (Nitrogen removal treatment) Ion-exchanged water was added to the phosphorylated pulp to prepare a slurry with a solid content of 4% by mass. The slurry was adjusted to pH 13.4 by adding 48% by mass of sodium hydroxide aqueous solution, and heated at a liquid temperature of 85°C for 1 hour. The pulp slurry was then dehydrated, and 10 L of ion-exchanged water was poured into 100 g of phosphorylated pulp (bone dry mass) to obtain a pulp dispersion. The pulp was stirred so that the pulp was uniformly dispersed, and the filtration and dehydration were repeated to remove excess sodium hydroxide. The end point of the removal was when the electrical conductivity of the filtrate became 100 μS / cm or less. The amount of carbamide groups introduced, obtained from the amount of nitrogen measured by the measurement method described below, was 0.01 mmol / g.
[0167] The infrared absorption spectrum of the phosphorus oxyoxidized pulp obtained in this way was measured using FT-IR. -1 Absorption due to the P=O of phosphate groups was observed near the 2θ=14° to 17° position, and it was confirmed that phosphate groups had been added to the pulp. In addition, when the obtained phosphorylated pulp was used as a test sample and analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, and it was confirmed that cellulose type I crystals were maintained. The amount of phosphate groups (amount of first dissociated acid) measured by the measurement method described below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0168] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose.
[0169] (Substituent removal treatment (high temperature heat treatment)) The fine fibrous cellulose dispersion was placed in a pressure vessel and heated at 160°C for 15 minutes until the amount of phosphate groups reached 0.08 mmol / g. This operation confirmed the formation of fine fibrous cellulose aggregates.
[0170] (Cleaning of slurry after removing substituents) The slurry after heating was washed by repeatedly adding the same amount of ion-exchanged water as the slurry to make a slurry with a solid content concentration of about 1% by mass, stirring the slurry, and then filtering and dehydrating it. When the electrical conductivity of the filtrate became 10 μS / cm or less, ion-exchanged water was added again to make a slurry with a solid content of about 1% by mass, and the slurry was left to stand for 24 hours. The operation of filtering and dehydrating was further repeated from there, and the washing end point was when the electrical conductivity of the filtrate became 10 μS / cm or less again. Ion-exchanged water was added to the obtained fine fibrous cellulose aggregate, and a slurry was obtained after removing the substituents. The solid content concentration of this slurry was 1.7% by mass.
[0171] (Uniform dispersion of slurry after removing substituents) Ion-exchanged water was added to the obtained slurry after the removal of substituents to make the slurry have a solid content of 1.0% by mass, and the slurry was treated three times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a dispersion of the substituent-removed fine fibrous cellulose containing the substituent-removed fine fibrous cellulose. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 2 to 4 nm.
[0172] (Measurement of phosphorus oxoacid group content) The amount of phosphorus oxo acid groups (equal to the amount of phosphorus oxo acid groups in phosphorus oxoxidized (phosphorylated or subphosphorylated) pulp) was measured by adding ion-exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to prepare a slurry containing 0.2 mass% of fine fibrous cellulose, treating the resulting slurry with an ion-exchange resin, and then titrating it with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the ion exchange resin from the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution to the slurry containing fine fibrous cellulose after the treatment with ion exchange resin every 5 seconds, while measuring the change in the pH value of the slurry. The titration was performed while blowing nitrogen gas into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the derivative value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the addition of alkali is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 1). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point divided by the solid content (g) in the slurry to be titrated was defined as the amount of phosphorus oxo acid group (mmol / g). The amount of alkali (mmol) required from the start of titration to the second end point divided by the solid content (g) in the slurry to be titrated was defined as the total amount of dissociated acid (mmol / g). The amount of phosphorus oxoacid groups (amount of phosphorus oxoacid groups introduced) (mmol / g) indicates the amount of substituents per 1 g of fine fibrous cellulose when the counter ion of the phosphorus oxoacid group is a hydrogen ion (H+). <Example 1> [Preparation of Sheet 1] (Formation of adhesive layer 1B) 8.5 parts by mass of modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Inc., Iupizeta RX-2136P) and 90 parts by mass of toluene were mixed. Next, 1.5 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, Duranate TPA-100) was added as an adhesion assistant and mixed to obtain a resin coating liquid. This resin coating liquid was applied to a resin film 1 (polyethylene terephthalate film, Toyobo Co., Ltd., Cosmoshine A4160, thickness 250 μm) with a Mayer bar so that the coating thickness was 5 μm. Thereafter, it was dried at 80 ° C for 5 minutes to obtain a resin film 1 provided with an adhesive layer 1B.
[0173] (Formation of fine fibrous cellulose-containing layer 1) Hydroxypropyl methylcellulose (Metolose 65SH-1500, Shin-Etsu Chemical Co., Ltd.) was added to ion-exchanged water to a concentration of 2% by mass, and the mixture was stirred at room temperature for 1 hour to dissolve. By the above procedure, an aqueous cellulose ether solution was obtained. The fine fibrous cellulose dispersion obtained in Production Example 1 and the above cellulose ether aqueous solution were each diluted with ion-exchanged water so that the solid content concentration was 1.6% by mass. Then, 70 parts by mass of the diluted fine fibrous cellulose dispersion and 30 parts by mass of the diluted cellulose ether aqueous solution were mixed to obtain a mixed solution. Furthermore, the finished basis weight of the fine fibrous cellulose-containing layer 1 was 45 g / m 2 The mixture was weighed out so that the thickness of the adhesive layer 1B was 100 μm, and the adhesive layer 1B was coated with the mixture. The mixture was then dried at 80° C. for 1 hour and aged at 90° C. for 8 hours. The thickness of the fine fibrous cellulose-containing layer 1 was 35 μm. By the above procedure, a sheet 1′ (layer structure: fine fibrous cellulose-containing layer 1-adhesive layer 1B-resin film 1) was obtained.
[0174] (Formation of adhesive layer 1A) The resin coating solution prepared in the above (Formation of adhesive layer 1B) was applied to the fine fibrous cellulose-containing layer 1 of sheet 1' with a Mayer bar to a coating thickness of 5 μm. Then, it was dried at 80° C. for 5 minutes and aged at 90° C. for 8 hours. Through the above procedure, sheet 1 (layer structure: adhesive layer 1A-fine fibrous cellulose-containing layer 1-adhesive layer 1B-resin film 1) was obtained.
[0175] [Preparation of Sheet 2] In the same manner as in the case of the sheet 1, a sheet 2 (layer structure: adhesive layer 2A--fine fibrous cellulose-containing layer 2--adhesive layer 2B--resin film 2) was prepared. The thickness of each layer constituting sheet 2 is the same as the thickness of each layer constituting sheet 1.
[0176] [Formation of Laminate] The sheet 1 was placed on one side of a polycarbonate plate (Teijin Co., Ltd., Panlite PC-1151, thickness 3,000 μm) with dimensions of 150 × 150 mm as a core resin plate so that the adhesive layer 1A was in contact. The sheet 2 was placed on the opposite side of the polycarbonate plate to the side on which the sheet 1 was placed so that the adhesive layer 2A was in contact. Next, this was sandwiched between two stainless steel plates with a thickness of 2 mm and dimensions of 200 × 200 mm. Thereafter, it was inserted into a mini test press (Toyo Seiki Kogyo Co., Ltd., MP-WCH) and heated to 160 ° C. over 1 minute under a press pressure of 5 MPa. Furthermore, it was held in this state for 1 minute and then cooled to 30 ° C. over 1 minute. By the above procedure, a laminate having a layer structure shown in Table 1 was obtained.
[0177] <Example 2> In Example 1 (formation of the fine fibrous cellulose-containing layer 1), the finished basis weight of the fine fibrous cellulose-containing layer 1 was 90 g / m 2 A laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 1, except that the above was used.
[0178] <Example 3> In Example 1 (formation of the fine fibrous cellulose-containing layer 1), the finished basis weight of the fine fibrous cellulose-containing layer 1 was 135 g / m2 A laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 1, except that the above was used.
[0179] <Example 4> In Example 1 (formation of the fine fibrous cellulose-containing layer 1), the finished basis weight of the fine fibrous cellulose-containing layer 1 was 180 g / m 2 A laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 1, except that the above was used.
[0180] <Example 5> In Example 1 (formation of the fine fibrous cellulose-containing layer 1), the finished basis weight of the fine fibrous cellulose-containing layer 1 was 225 g / m 2 A laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 1, except that the above was used.
[0181] <Example 6> In Example 5 (formation of adhesive layer 1B), a laminate having the layer structure shown in Table 1 was obtained in the same manner as Example 5, except that a polymethyl methacrylate film (Sumika Acrylic Co., Ltd., Technoloy Film S001G, thickness 250 μm) was used as the resin film 1 instead of the polyethylene terephthalate film. As the resin film 2, a polymethyl methacrylate film (Sumika Acryl Co., Ltd., Technoloy Film S001G, thickness 250 μm) was used in place of the polyethylene terephthalate film.
[0182] <Comparative Example 1> In Example 1 (formation of adhesive layer 1B), except that a polycarbonate film (AGC Corporation, Carboglass, thickness 250 μm) was used as the resin film 1 instead of the polyethylene terephthalate film, a laminate having the layer structure shown in Table 1 was obtained in the same manner as Example 1.
[0183] <Comparative Example 2> In Example 3 (formation of adhesive layer 1B), except that a polycarbonate film (AGC Corporation, Carboglass, thickness 250 μm) was used as the resin film 1 instead of the polyethylene terephthalate film, a laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 3.
[0184] <Comparative Example 3> In Example 5 (formation of adhesive layer 1B), except that a polycarbonate film (AGC Corporation, Carboglass, thickness 250 μm) was used as the resin film 1 instead of the polyethylene terephthalate film, a laminate having the layer structure shown in Table 1 was obtained in the same manner as in Example 5.
[0185] <Comparative Example 4> A laminate was obtained in the same manner as in Example 5, except that in (formation of adhesive layer 1B) of Example 5, a polycarbonate film (AGC Corporation, Carboglass, thickness 250 μm) was used as the resin film 1 instead of the polyethylene terephthalate film, and in (production of the laminate), a polymethyl methacrylate plate (Kuraray Co., Ltd., Paraglass, thickness 3,000 μm) was used as the core resin plate instead of the polycarbonate plate.
[0186] <Comparative Example 5> [Preparation of sheet 1a] An aqueous cellulose ether solution and a mixed solution were obtained in the same manner as in Example 1 (formation of fine fibrous cellulose-containing layer 1). The finished basis weight of the fine fibrous cellulose-containing layer 1 is 225 g / m 2 The mixture was weighed so that the thickness of the mixture became 100 μm, and then coated on a polyester film (Toyobo Co., Ltd., Cosmoshine A4160, thickness 250 μm). Then, the film was dried at 80° C. for 1 hour to form a layer 1 containing fine fibrous cellulose. A resin coating liquid was obtained in the same manner as in (formation of adhesive layer 1B) of Example 1. This resin coating liquid was applied to the fine fibrous cellulose-containing layer 1 with a Mayer bar to a coating thickness of 5 μm to form an adhesive layer 1B. The polyester film was peeled off from the fine fibrous cellulose-containing layer 1, and the above-mentioned resin coating liquid was applied to the surface of the fine fibrous cellulose-containing layer 1 that had been in contact with the polyester film using a Mayer bar so that the coating thickness was 5 μm. Then, the layer was dried at 80° C. for 5 minutes and aged at 90° C. for 8 hours. By the above procedure, a sheet 1a (layer structure: adhesive layer 1A-fine fibrous cellulose-containing layer 1-adhesive layer 1B) was obtained. [Preparation of sheet 2a] Sheet 2a (layer structure: adhesive layer 2A-fine fibrous cellulose-containing layer 2-adhesive layer 2B) was prepared in the same manner as sheet 1a. The thickness of each layer constituting sheet 2a was the same as that of each layer constituting sheet 1a. [Laminate formation] A laminate having the layer structure shown in Table 1 was obtained in the same manner as in [Formation of a laminate] of Example 1, except that in [Formation of a laminate] of Example 1, sheets 1a and 2a were used instead of sheets 1 and 2.
[0187] <Comparative Example 6> An attempt was made to produce a laminate having the layer structure shown in Table 1 in the same manner as in Example 1, except that no adhesive layer was formed, but no laminate was obtained.
[0188] <Comparative Example 7> [Preparation of sheet 1b] A resin coating liquid was obtained in the same manner as in Example 1 (formation of fine fibrous cellulose-containing layer 1). This resin coating liquid was applied to a polycarbonate film (AGC Corporation, Carboglass, thickness 250 μm) with a Mayer bar to a coating thickness of 5 μm, and dried at 80 ° C for 5 minutes to form an adhesive layer 1B. The resin coating liquid was applied to the adhesive layer 1B with a Mayer bar to a coating thickness of 5 μm, and dried at 80 ° C for 5 minutes to obtain a sheet 1b (layer structure: adhesive layer 1A-adhesive layer 1B-resin film 1). [Preparation of sheet 2b] Sheet 2b (layer structure: adhesive layer 2A-adhesive layer 2B-resin film 2) was produced in the same manner as sheet 1b. The thickness of each layer constituting sheet 2b was the same as that of each layer constituting sheet 1b. [Laminate formation] A laminate having the layer structure shown in Table 1 was obtained in the same manner as in [Formation of a laminate] of Example 1, except that in [Formation of a laminate] of Example 1, sheets 1b and 2b were used instead of sheets 1 and 2.
[0189] <Measurement and evaluation of laminate properties> [Total light transmittance of laminate] A test piece measuring 50 mm square was cut out from the laminate. The total light transmittance was measured using this test piece in accordance with JIS K 7361-1:1997 using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.). The results are shown in Table 1.
[0190] [Haze of laminate] A test piece measuring 50 mm square was cut out from the laminate. The haze of this test piece was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136:2000. The results are shown in Table 1.
[0191] [Yellowness measurement of laminate] The yellowness index (YI) of the laminate was measured using Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K 7373:2006. The results are shown in Table 1.
[0192] [Flexural strength and flexural modulus of laminate] The laminate was cut into a rectangular test piece measuring 80 mm in length and 10 mm in width, and a three-point bending test was performed in accordance with JIS K 7171:2016. The bending strength and bending modulus were evaluated as being superior in rigidity and strength against bending, respectively, as the values were higher. The test was performed at 23°C. The results are shown in Table 1.
[0193] [Linear thermal expansion coefficient of laminate] A test piece measuring 5 mm in length and 5 mm in width was cut out from the laminate. Using this test piece, a thermomechanical analyzer (Hitachi High-Tech Science Corporation, TMA7100) was used to measure the change in length of the test piece under conditions of a temperature range of 25 to 110°C and a heating rate of 5°C / min, and the linear thermal expansion coefficient (ppm / K) was calculated by dividing the change in length in a temperature range of 30 to 80°C by the change in temperature. The results are shown in Table 1.
[0194] [Tensile modulus of resin films 1 and 2] A rectangular test piece (type 2) was cut from each of the resin films 1 and 2, and a tensile test was carried out in accordance with JIS K 7127:1999. [Tensile modulus of elasticity of core resin plate] A dumbbell-shaped test piece (1A) was cut from the core resin plate, and a tensile test was performed in accordance with JIS K 7161-2:2014.
[0195] [Table 1]
[0196] (Explanation of abbreviations in the table) PET: Polyethylene terephthalate PC: Polycarbonate PMMA: Polymethyl methacrylate CNF layer: A layer containing fine fibrous cellulose (Explanation of notes in the table) *1: Thickness of resin film 1 and resin film 2 *2: Tensile modulus of resin film 1 and resin film 2 *3: Tensile modulus of elasticity of resin film 1 (or resin film 2) - Tensile modulus of elasticity of core resin plate (Since resin films 1 and 2 are the same resin film, "tensile modulus of resin film 1 - tensile modulus of core resin plate" and "tensile modulus of resin film 2 - tensile modulus of core resin plate" are the same value.) *4: Thickness of CNF layer 1 and CNF layer 2 *5: 100 x total thickness of CNF layer 1 and CNF layer 2 / thickness of laminate
[0197] From Table 1, it can be seen that the laminates (Examples 1 to 6) having the layer structure defined in the present invention and in which the tensile modulus of elasticity of resin film 1 and the tensile modulus of elasticity of resin film 2 are greater than the tensile modulus of elasticity of the core resin plate have superior rigidity (flexural strength and flexural modulus) compared to the laminates of Comparative Examples 1 to 7.
Claims
1. A laminate comprising: an adhesive layer 1A, a fine fibrous cellulose-containing layer 1 containing fine fibrous cellulose having a fiber width of 1000 nm or less, an adhesive layer 1B, and a resin film 1 laminated in this order on one surface of a core resin plate; and an adhesive layer 2 and a resin film 2 laminated in this order on a surface of the core resin plate opposite to the surface having the resin film 1, The core resin plate contains polycarbonate resin, A laminate in which the tensile modulus of elasticity of resin film 1 and the tensile modulus of elasticity of resin film 2 are greater than the tensile modulus of elasticity of the core resin plate.
2. 2. The laminate according to claim 1, wherein the tensile modulus of elasticity of the resin film 1 and the tensile modulus of elasticity of the resin film 2 are greater than the tensile modulus of elasticity of the core resin plate by 0.5 GPa or more.
3. 3. The laminate according to claim 1, wherein the resin film 1 and the resin film 2 each contain at least one selected from the group consisting of polyethylene terephthalate and polymethyl methacrylate.
4. 3. The laminate according to claim 1, wherein the adhesive layer 1A and the adhesive layer 1B contain at least one resin selected from the group consisting of a polycarbonate-based resin, an acrylic-based resin, and a polyester-based resin.
5. 3. The laminate according to claim 1, wherein the adhesive layer 1A and the adhesive layer 1B are formed from an adhesive composition containing an isocyanate compound.
6. 3. The laminate according to claim 1, wherein the thickness of the core resin plate is from 500 μm to 3,500 μm.
7. 3. The laminate according to claim 1, wherein the thickness of the fine fibrous cellulose-containing layer 1 is from 20 μm to 300 μm.
8. 3. The laminate according to claim 1, wherein the resin film has a thickness of 30 μm or more and 500 μm or less.
9. 3. The laminate according to claim 1 or 2, which is obtained by laminating, in the order listed, an adhesive layer 2A, a fine fibrous cellulose-containing layer 2 containing fine fibrous cellulose having a fiber width of 1000 nm or less, an adhesive layer 2B, and a resin film 2 on the surface of the core resin plate opposite to the surface having the resin film 1.
10. 10. The laminate according to claim 9, wherein the adhesive layer 2A and the adhesive layer 2B contain at least one resin selected from the group consisting of a polycarbonate-based resin, an acrylic-based resin, and a polyester-based resin.
11. 10. The laminate according to claim 9, wherein the adhesive layer 2A and the adhesive layer 2B are formed from an adhesive composition containing an isocyanate compound.
12. 10. The laminate according to claim 9, wherein the thickness of the fine fibrous cellulose-containing layer 2 is 20 μm or more and 250 μm or less.
13. 3. The laminate according to claim 1, wherein the resin film has a thickness of 30 μm or more and 500 μm or less.
14. The laminate according to claim 1 or 2, having a flexural modulus of 3.4 GPa or more.
Citation Information
Patent Citations
JP1974085573A